Blamestorming, Blamemongers and Scapegoats Allocating blame in the criminal justice process - Dingwall, Gavin (2015)
Available Open Access under CC-BY-NC-ND licence We live in a society that is increasingly preoccupied with allocating blame: when something goes wrong someone must be to blame. Bringing together philosophical, psychological, and sociological accounts of blame, this is the first detailed criminological account of the role of blame in which the authors present a novel study of the legal process of blame attribution, set in the context of criminalisation as a social and political process. This timely and topical book will be essential reading for anyone working or researching in the criminal justice field. It will also be of wider interest to anyone wishing to discover the role of blame in modern society.